2016
DOI: 10.1111/anec.12388
|View full text |Cite
|
Sign up to set email alerts
|

Frontal QRS-T Angle and the Risk of Atrial Fibrillation in the Elderly

Abstract: Background Frontal QRS-T angle reflects changes in regional action potential duration and the direction of repolarization. Although it has been suggested that abnormal ventricular repolarization predisposes to atrial arrhythmias, it is unknown whether abnormal frontal QRS-T angle is associated with an increased risk of atrial fibrillation (AF). Methods We examined the association between frontal QRS-T angle and AF in 4,282 participants (95% white; 41% male) from the Cardiovascular Health Study (CHS). QRS-T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…22,23 However, no study has investigated the impact of antiarrhythmic drugs on frontal plane QRS-T angle. Because increase in frontal plane QRS-T angle predicts arrhythmia and arrhythmic death, 9,12 it is reasonable to investigate the impact of antiarrhythmic drugs on frontal plane QRS-T angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 However, no study has investigated the impact of antiarrhythmic drugs on frontal plane QRS-T angle. Because increase in frontal plane QRS-T angle predicts arrhythmia and arrhythmic death, 9,12 it is reasonable to investigate the impact of antiarrhythmic drugs on frontal plane QRS-T angle.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Importantly, increased frontal plane QRS-T angle seems to be associated with an increased risk for Af development independent of well-known Af risk factors. 12 However, no study has investigated the importance and usefulness of frontal plane QRS-T angle in patients with a recent-onset Af episode. Moreover, although amiodarone can cause various changes in electrocardiography (ECG), the impact of intravenous amiodarone infusion on frontal plane QRS-T angle has not been demonstrated yet.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…The f(QRS‐T) angle was calculated from these axes as absolute difference between frontal plane QRS axis and frontal plane T axis. If the angle exceeds 180°, it was calculated by subtracting from 360 o (Jogu et al., ; Macfarlane, ; Oehler et al., ; Zhang et al., ). Because our calculation of f(QRS‐T) angle was based on automatic report of ECG machine, the subjective component of the individual measurements have been eliminated.…”
Section: Methodsmentioning
confidence: 99%
“…The QRS/T angle is a sensitive and reproducible marker of abnormal ventricular depolarization and repolarization which is able to detect depolarization and repolarization abnormalities before other common markers are apparent as QRS duration or QT interval [1316]. Abnormal ventricular repolarization is an established mechanism for arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A decade ago, we first reported that the frontal plane QRS/T angle was a ‘suitable clinical substitute’ for spatial QRS/T angle with respect to CHD risk prediction in the ARIC study [12]. Since then, the frontal QRS/T angle has been intensively studied in various populations, as a predictor of different outcomes including heart failure, atrial fibrillation, sudden cardiac death, and all-cause mortality [1618,2426]. Our study adds SMI to this list of outcomes, for the first time.…”
Section: Discussionmentioning
confidence: 99%